Pembinaan Akhlakul Karimah Peserta Didik melalui Kegiatan Shalat Duha di MI Darussalam Kelas V - Agung Purwono; Khaerul Arif Jazak Shabana (MISOOL: Jurnal Pendidikan Dasar, 2022)
This study discusses the development of akhlakul karimah students at MI Darussalam Pacet through duha prayer activities. The background of this research is in order to foster the morals of students through Duha prayer activities. Given the importance of prayer, it is very necessary to instill it in students from an early age. The approach used in this study is a qualitative approach, research that produces descriptive data, with the type of case study research. This research was conducted in class V with the subject of the principal, 1 class teacher, and 4 parents of students. Data collection techniques used are interviews, observation, and documentation. While the analysis is through the stages of reduction, data presentation, and conclusions. After conducting research, it was found that the Duha prayer at MI Darussalam Pacet had gone well. The impact of implementing Duha prayer activities on the morals of students includes time discipline, patience, courtesy, and mutual respect. While there are interesting things found in the Duha prayer at home, namely the participation of other family members to carry out the Duha prayer. From the results of the study, it can be concluded that coaching through Duha prayer activities brings many benefits and positive impacts to the daily lives of students.